PSI-19 Effect of Increasing Supplementation of Bacillus Spp. on in Vitro Ruminal Fermentation and Nutrient Digestibility. (21st September 2022) - Maderal, Araceli; Fernandez-Marenchino, Ignacio; Cuervo, Wilmer; Tarnonsky, Federico; Podversich, Federico; de Martinez, Juan Jesus Vargas; Moreno, Martin Ruiz; Schulmeister, Tessa M; Queiroz, Oscar; Cappellozza, Bruno; DiLorenzo, Nicolas
Abstract: Probiotics may be an effective alternative to antimicrobials in terms of modifying the ruminal microbial ecology to enhance the fermentative process and improving animal health and production. Although Bacillus spp. have demonstrated a great potential, the effects of increasing inclusion levels on ruminal fermentation profile are unclear. The objective of this study was to evaluate the effects of increasing doses of a Bacillus spp. probiotic on in vitro ruminal fermentation profile, gas production kinetics, and nutrient digestibility, using a sorghum silage-based substrate. Incubations were conducted in sixteen separate days during 12 and 24 h. Treatments were: Sorghum-silage only (Control) or sorghum silage + one of three doses of a Bacillus spp. probiotic included at 1, 5 and 10 times the recommended dose (8 × 10 4 CFU/ml). Ruminal fluid was collected from two ruminally cannulated steers fed an ad libitum corn silage-based diet. Gas production kinetics, pH, in vitro true digestibility, digestibility of neutral and acid detergent fiber, methane (CH4 ) production and concentration of volatile fatty acids (VFA) and ammonia nitrogen (NH3 -N) were measured after 24 h of incubation. Digestibility of starch was measured at 12 h of incubation. Inclusion of Bacillus spp. did not affect (P > 0.05) rumen nutrient digestibility or pH. Concentration of NH3 -N and total VFA increased quadratically (P < 0.05) with the probiotic inclusion. Inclusion of Bacillus spp. decreased molar proportions of acetate (P < 0.01) but increased molar proportion of propionate (P = 0.02). Total gas production and CH4 emissions were not affected (P > 0.05) by the probiotic inclusion, while rate of gas production increased quadratically as probiotic dose increased (P < 0.01). These in vitro dose-dependent effects of probiotic inclusion show promissory results based on total and molar VFA proportions; however, these results should be evaluated in vivo.